Interactive Arabic Vocabulary Learning Through Crossword Puzzles in Elementary School: Pembelajaran Kosakata Arab Interaktif Melalui Teka-teki Silang di Sekolah Dasar - Ardiansah , Adam Nur; Hikmah, Khizanatul (Universitas Muhammadiyah Sidoarjo, 2025)
Background: Arabic language is a core subject in Islamic education, yet students often face difficulties in mastering vocabulary. Specific Background: At SD Muhammadiyah 1 Trenggalek, vocabulary learning was often monotonous, reducing students’ interest. Knowledge Gap: Previous studies rarely focused on systematic integration of crossword puzzles (TTS) as a structured medium for vocabulary instruction. Aim: This study aims to describe the process, challenges, and solutions of implementing TTS in Arabic vocabulary learning. Results: The findings show that TTS increases students’ participation, memory retention, and contextual understanding of vocabulary. Challenges include limited class time, diverse student abilities, and low initial engagement. Novelty: The study proposes strategies such as pictorial TTS, audiovisual support, step-by-step implementation, rewards, and teacher training. Implications: These results provide practical recommendations for teachers to design interactive and student-centered vocabulary learning in elementary schools. Highlights:• TTS fosters active and contextual Arabic vocabulary learning• Solutions address time, ability gaps, and motivation issues• Practical strategies proposed for sustainable classroom implementation Keyword: Arabic Vocabulary, Crossword Puzzle, Elementary School, Interactive Learning, Teacher Strategy